The Influence of Mnemonic Pictures and Attitudes toward the Students’ Writing Achievement of the Eighth Grade Students of SMP PGRI 1 Palembang - Etty Pratiwi (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACT This research investigated the influence of Mnemonic Pictures and attitudes toward the students’ writing achievement of the Eighth Grade Students of SMP PGRI 1 Palembang. The problems of this study were to identify whether or not (1) there is a significant difference in average of writing achievement between the students who are in positive attitude after being taught using mnemonic pictures strategy and those who are taught using conventional strategy;(2) there is a significant difference in average of writing achievement between the students who are in negative attitude after taught using mnemonic pictures strategy and those who are taught using conventional strategy; (3) there is a significant difference in average of writing achievement between the students who are in positive and negative attitude after being taught using mnemonic pictures strategy and those who are taught using conventional strategy;and (4) there is a significant interaction effect of mnemonic pictures strategy and attitude on the students’ writing achievement. This study was conducted in experimental research to 96 students of SMP PGRI 1 Palembang in the first semester of the academic year of 2013-2014. This study could be concluded that mnemonic pictures strategy and attitudes gave a significant influence for the students’ writing achievement since there was a significant improvement in average of the students’ writing achievement before and after being taught using mnemonic pictures strategy. Keywords: mnemonic pictures, attitudes, and writing achievement